EFFECT OF FOAM ROLLER AND STATIC STRETCHING ON BIOMECHANICAL PARAMETERS OF MUSCLE - Ciematnieks, Uģis; Tomanoviča, Evita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
After training, it is needed to perform flexibility exercises for muscle stretching, but many choose to use the foam roller. With a foam roller, you can both exercise and perform a myofascial release that affects the deep tissues of extremities. Myofascial release improves blood circulation in muscle, develops elasticity, flexibility and minimizes the risk of an unwanted injury (Myers & Frederick, 2012). Many studies are being carried out to determine the effects of the various types of stretching on balance, speed and reaction (Apostolopoulos, Metisos, Flouris & Koutedakis, 2015). Training programs are designed so that after applying different workloads at the end there is cool-down through stretching exercises, but these training plans rarely recommends foam rollers as stretching means, even though they are popular every day. Aim of study: Find out the most effective method for reducing muscle tension in lower extremities. The study identifies changes in the biomechanical parameters of the hamstring muscle group after general stretching exercises and foam roller, after GRIP fitness concept class, using the Myoton PRO biomechanical parameters measurement. The study do not show any significant differences that may be in favour of one or the other method. Literature sources indicate that foam rollers exercises helps to relieve and restore the strained muscles more quickly, increases flexibility (Barrett, 2017). Our study did not confirm any of such findings. Foam roller exercises for myophascial release is as effective as static stretching exercises.